2005
DOI: 10.1074/jbc.m504678200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of the Blockade of Plasma Cholesteryl Ester Transfer Protein by Its Physiological Inhibitor Apolipoprotein CI

Abstract: Genetically engineered mice demonstrated that apolipoprotein (apo) CI is a potent, physiological inhibitor of plasma cholesteryl ester transfer protein (CETP) activity. The goal of this study was to determine the molecular mechanism of the apoCI-mediated blockade of CETP activity. Kinetic analyses revealed that the inhibitory property of apoCI is independent of the amount of active CETP, but it is tightly dependent on the amount of high density lipoproteins (HDL) in the incubation mixtures. The electrostatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
47
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 48 publications
6
47
0
Order By: Relevance
“…Either total plasma or purifi ed CETP was used as a source of cholesteryl ester transfer activity, with the interference or not of endogenous lipoproteins, as previously described ( 19,23,24,29 ). In the lipoproteinindependent assay, a source of CETP was incubated with labeled liposome donors and exogenous lipoprotein acceptors in excess.…”
Section: Fluorescent Cholesteryl Ester Transfer Assaymentioning
confidence: 99%
See 3 more Smart Citations
“…Either total plasma or purifi ed CETP was used as a source of cholesteryl ester transfer activity, with the interference or not of endogenous lipoproteins, as previously described ( 19,23,24,29 ). In the lipoproteinindependent assay, a source of CETP was incubated with labeled liposome donors and exogenous lipoprotein acceptors in excess.…”
Section: Fluorescent Cholesteryl Ester Transfer Assaymentioning
confidence: 99%
“…For apolipoprotein analysis, delipidated HDL proteins were applied on 4-12% SDS-polyacrylamide gels, and the apparent molecular weights of protein bands were determined by reference to protein standards ( 23 ). For the determination of electrophoretic mobility, native HDLs were applied on 0.5% agarose gels, and surface potentials (mV) were calculated from electrophoretic velocity as previously described ( 23,30 ).…”
Section: Electrophoretic Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Apolipoprotein C-I, which resides primarily on HDL, has been reported to inhibit CETP in vitro, and studies with transgenic animals have demonstrated its ability to suppress CETP activity in vivo (6,7). Its mode of action is via modification of the surface charge of HDL, resulting in weakened CETP-HDL interactions and thus suppression of lipid transfer events with HDL (8). A second regulatory protein is lipid transfer inhibitor protein (LTIP), also known as apolipoprotein F (9).…”
mentioning
confidence: 99%